2019
DOI: 10.5937/ekonomika1902013j
|View full text |Cite
|
Sign up to set email alerts
|

Kaizen as a global business philosophy for continuous improvement of business performance

Abstract: Today, numerous tools can be used in the production and other phase of the value chain with the aim of increasing operational efficiency and quality of products. However, the Kaizen can be understood as one of the basic lean techniques. Continuous improvement applied through Kaizen is a key element of Japanese management and the source of competitiveness. The benefits of an effective program of continuous improvement are reflected in cost efficiency, waste reduction and product quality improvement. Taught by J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…Different scholars also identified Kaizen practices as independent variables: leadership or top management support (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Jalu, 2015; Beshah and Kitaw, 2014); Customer focus (Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); People management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016); Process management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); Continuous improvement (Rawashdeh, 2018; Baye and Raju, 2016); Product design (Psomas et al , 2014); Supplier quality management (Rawashdeh, 2018; Baye and Raju, 2016); Strategy (policy, strategic planning) (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018); Resources including partnership (Shafiq et al , 2019; Beshah and Kitaw, 2014); Measurement, analysis and knowledge management (Jong et al , 2019; Rawashdeh, 2018); Kaizen tools and techniques (Jalu, 2015). Moreover, other preceding studies also identified Kaizen practices as CSFs: leadership (Janjić et al , 2019; Hailu et al , 2017b); Top management policy, commitment, support (Kumar, 2019; Lina and Ullah, 2019; Todorovic et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); process control (2017b); Culture of effective and flexible suggestion system (Kumar, 2019; Abdulmouti, 2018; Hailu et al , 2017b); the use of problem-solving approach (Kumar, 2019; Abdulmouti, 2018; Khanna et al , 2017a, b; Amrutkar and Kamalja, 2017) and Supportive organization structure (Kumar, 2019; Janjić et al , 2019); employee's attitude (Hailu et al , 2017b); employee's and management involvement, team dynamics (good presentation and communication skills), recognition (Janjić et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); good management–employee relationship and train employees (T...…”
Section: Literature Reviewmentioning
confidence: 87%
“…Different scholars also identified Kaizen practices as independent variables: leadership or top management support (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Jalu, 2015; Beshah and Kitaw, 2014); Customer focus (Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); People management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016); Process management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); Continuous improvement (Rawashdeh, 2018; Baye and Raju, 2016); Product design (Psomas et al , 2014); Supplier quality management (Rawashdeh, 2018; Baye and Raju, 2016); Strategy (policy, strategic planning) (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018); Resources including partnership (Shafiq et al , 2019; Beshah and Kitaw, 2014); Measurement, analysis and knowledge management (Jong et al , 2019; Rawashdeh, 2018); Kaizen tools and techniques (Jalu, 2015). Moreover, other preceding studies also identified Kaizen practices as CSFs: leadership (Janjić et al , 2019; Hailu et al , 2017b); Top management policy, commitment, support (Kumar, 2019; Lina and Ullah, 2019; Todorovic et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); process control (2017b); Culture of effective and flexible suggestion system (Kumar, 2019; Abdulmouti, 2018; Hailu et al , 2017b); the use of problem-solving approach (Kumar, 2019; Abdulmouti, 2018; Khanna et al , 2017a, b; Amrutkar and Kamalja, 2017) and Supportive organization structure (Kumar, 2019; Janjić et al , 2019); employee's attitude (Hailu et al , 2017b); employee's and management involvement, team dynamics (good presentation and communication skills), recognition (Janjić et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); good management–employee relationship and train employees (T...…”
Section: Literature Reviewmentioning
confidence: 87%
“…As stated by Lala;Ogada, et al (2019) an organization that has incorporated this theory is continually endeavoring to perfect its practices, uphold discipline and standardization, and considers the practices in areas for elucidating complications. Janjic, Bogicevic and Krstic (2019), concluded that, Kaizen is regarded as a valuable strategy for bettering performance and devices for perfecting the company and working environs leading to a long-term effect. It has demonstrated to be an actual instrument for altering the long-term orientation on work culture, working methods and work skill.…”
Section: Kaizen Theorymentioning
confidence: 99%
“…The Sino-Japanese word "kaizen" simply means "good change", neither of which has any intrinsic significance of "continuous" nor "philosophy" in dictionaries or in daily use in Japan. In the same way as the English word Debundked in Janjić, Bogićević, & Krstić (2019) believed that "improvement" applies to a one-time or continuous improvement, major or small, the term "improvement" refers to any improvement. However, provided Japan's custom of marking industrial or business improvement techniques with the term "kaizen" (due to a lack of a particular Japanese word with a specific meaning "continuous improvement" or "philosophy of improvement").…”
Section: The Original Meaning Of Kaizenmentioning
confidence: 99%
“…Healthcare Julie in (Daft, 2013), psychotherapy (Feldma, 1992), life coaching, government, banking, education (Simanjuntak, 2015), and other industries have all used it. Imai in Janjić, Bogićević, & Krstić (2019) argued that Kaizen refers to operations that continuously develop all roles and include all staff, from the CEO to assembly line personnel, when used in the corporate sense and extended to the workplace. It also refers to processes that cross organizational boundaries into the supply chain, such as buying and logistics.…”
Section: Kaizen Application In Other Fieldsmentioning
confidence: 99%